A bird's eye view of the synthesis and practical application of conducting polymers. Issue 4 (12th February 2018) - Evans, Drew
Abstract: For almost four decades conducting polymers (CPs) have maintained the interest of the global scientific community. This interest arises from the unique blend of properties that these materials possess: tuneable electrical properties combined with mechanical flexibility of traditional polymers. In more recent times the broader investigation of CP properties and behaviour has led to new potential applications, such as photovoltaic and bioelectronic devices. The promise of CPs is considerable, yet to date they have had limited penetration into the commercial and industrial sectors. This perspective article highlights some of the challenges and opportunities ahead as CPs translate from the research sector into commercial products. In particular is the need to study in depth the manufacturing process(es) of CPs and how they relate to existing or emerging industry. © 2018 The Author. Polymer International published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Despite significant attention from the research community, conducting polymers are yet to be commercialised. Potential applications do exist albeit with challenges aligning fabrication with properties and niche markets.